Caracterización morfológica de pasto King Grass “morado” (Pennisetum purpureum), en las condiciones edafoclimáticas de Babahoyo - Lindao Vera, Geovanny Darío (2020)
This research was carried out with the purpose of morphologically describing the "purple" King Grass (Pennisetum purpureum), under the agro-ecological conditions of the Babahoyo canton. Morphological diversity was analyzed in a sample size of 16 individuals located within the Faculty of Agricultural Sciences of the Technical University of Babahoyo located in Babahoyo province of Los Ríos. To evaluate the variability of phenotypic characteristics of the King Grass pasture, adapters used for other studies of the same nature were adapted. As results, it was possible to show that there are no phenotypic differences in the evaluated ecotypes of "purple" King Grass (Pennisetum purpureum), since none of the variables exceeded a Cv> 50%, indicating that the species has little variability. Regarding the correlation coefficient, the results show a relationship between the evaluated variables, where it was possible to determine that there are variables that are related such as: the weight of the leaf with the height of the plant with a value of 0.63; Likewise, a relationship between leaf width and stem diameter was evidenced with a value of 0.59. On the other hand, the analysis also shows a strong relationship between dry weight and wet weight with a value of 0.92.